2018
DOI: 10.1158/1538-7445.am2018-lb-127
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-127: From bench to bedside: Exploring OX40 receptor modulation in a phase 1/2a study of the OX40 costimulatory agonist BMS-986178 ± nivolumab (NIVO) or ipilimumab (IPI) in patients with advanced solid tumors

Abstract: Background: Activation of OX40, a costimulatory protein in the tumor necrosis factor receptor super family, enhances T effector cell activation and inhibits T regulatory (Treg) cell-mediated suppression. Preclinical data showed that combination of an OX40 agonist with checkpoint blockade (anti-PD-1 or anti-CTLA-4) enhanced antitumor activity vs checkpoint blockade alone. BMS-986178 is a fully human IgG1 agonist monoclonal antibody that binds with high affinity to OX40 and was well tolerated ± NIVO (anti-PD-1; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Several OX40 agonists have now reached early-stage clinical development as monotherapy and combination therapy, including MOXR0916, PF-04518600, BMS-986178, INCAGN01949, and GSK3174998 (6,39). A combination trial of MEDI0562 with durvalumab (anti-PD-L1) and with tremelimumab (anti-CTLA-4) to treat advanced solid tumors is currently ongoing (NCT02705482).…”
Section: Discussionmentioning
confidence: 99%
“…Several OX40 agonists have now reached early-stage clinical development as monotherapy and combination therapy, including MOXR0916, PF-04518600, BMS-986178, INCAGN01949, and GSK3174998 (6,39). A combination trial of MEDI0562 with durvalumab (anti-PD-L1) and with tremelimumab (anti-CTLA-4) to treat advanced solid tumors is currently ongoing (NCT02705482).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for selection of these doses has been described previously and was based on pharmacokinetic and pharmacodynamic modeling of the relationship between RO, pharmacodynamic modulation, and efficacy (28)(29)(30)(31). On the basis of preclinical data, available RO data from the every 2 weeks cohort receiving monotherapy, and C min (minimum plasma concentration after dosing) data at day 14 (trough sample), a mathematical model was developed to predict RO at various dosing regimens (e.g., every 4 weeks, every 6 weeks, and every 12 weeks), taking into account interpatient variability in both pharmacokinetics and pharmacodynamics (RO), to maximize the potentiation of T-cell responses (28,31).…”
Section: Translational Relevancementioning
confidence: 99%
“…Preclinical studies with the murine analogue OX40.23 as monotherapy demonstrated antitumor activity that was further enhanced when it was combined with checkpoint inhibitors (29). In the phase I clinical trial, the combination of BMS-986178 and nivolumab or ipilimumab demonstrated linear pharmacokinetics with dose-related increases in exposure (30). BMS-986178 monotherapy increased proinflammatory cytokines, such as IFNg and the IFNg-induced cytokines CXCL9 and CXCL10, in patients with advanced solid tumors, with greater effects observed after combination therapy (28).…”
Section: Introductionmentioning
confidence: 99%
“…A population pharmacokinetic model was developed by nonlinear mixed-effects modeling using data from 90 participants from monotherapy and combination cohorts in the first-inhuman clinical study of BMS-986178. The pharmacokinetics and pharmacodynamics of BMS-986178 was linear, and was described by a two-compartment, zero-order intravenous infusion with first-order elimination (17). Subsequently, a pharmacokineticpharmacodynamic analysis (E max model) was conducted to characterize the relationship between BMS-986178 concentrations and blood receptor occupancy using data from 19 patients treated with 20-320 mg BMS-986178 in the clinical study.…”
Section: Statistical Analysis and Pharmacokinetic-pharmacodynamic Analysismentioning
confidence: 99%